Evaluation of Teacher Performance in Learning in Public Elementary Schools Using the Charlotte Danielson Model - Eskris, Yosiana; Iriani, Ade (International Journal of Social Service and Research, 2023)
Teacher performance evaluation is the process of assessing and measuring a person's performance, which is always compared with the expected goals, objectives, and standards. The purpose of this study was to evaluate the performance of grade 3 and 6 elementary school teachers in learning using the Charlotte Danielson model. The type of research used is evaluation research, with descriptive methods and mixed-method approaches. The research was conducted at SDN Kutowinangun 07 and SDN Kutowinangun 08, Data collection techniques through observation, interviews, documentation, and teacher performance assessment questionnaires. To guarantee the validity of the data, researchers use triangulation of data sources and triangulation of methods. Data analysis techniques use qualitative descriptives to analyze data obtained from interviews, observations, and documents. Quantitative analysis is used to analyze numerical data from questionnaires filled out by teachers or peers. The results showed that the performance of grade 3 and 6 teachers of SDN Kutowinangun 07 and SDN Kutowinangun 08 in planning and preparing learning, managing classes, learning processes and in showing their professional responsibilities were included in the very good category. From the results of the four domains above, it can provide recommendations for principals to improve the performance weaknesses of each teacher and continue to develop teacher abilities.